TAX COMPLIANCE FOR MSMES CULINARY INDUSTRY: INFLUENCING FACTORS ANALYSIS - Aresteria, Maya; Sulestiyono, Deddy; Rakhmayani, Alfita (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
Business activities carried out by the community are inseparable from national development. MSMEs as a community forum in running a business, have a very influential role in the distribution of people's income. The government pays more attention to MSMEs, especially in developing and funding MSMEs. With the running of MSMEs, people's income will immediately increase, in line with the taxation that follows MSME income.Taxes are state revenues that are highly calculated as a source of state financing. By adhering to self-assessment, MSME actors as taxpayers carry out their own tax calculations, payments and reports. This study used MSME actors in Central Java as a sample using data collection methods through questionnaires, observations and interviews. Purposive sampling was used in determining the sample until 100 respondents were fulfilled. In this study, a sample of 100 MSME actors in Central Java was taken. Regression analysis is used in data processing. The results showed that the tax amnesty variable had no significant effect on taxpayer compliance, while the tax understanding and tax administration services variables had a significant effect on tax compliance.